2009
DOI: 10.1111/j.1365-2184.2009.00646.x
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical cord blood processing using Prepacyte‐CB increases haematopoietic progenitor cell availability over conventional Hetastarch separation

Abstract: These results show that PrepaCyte-CB offers superior separation of UCB when compared to Hetastarch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…The majority of CBBs employ growth‐based RMMs for sterility testing in place of the method recommended, described and specified in 21 CFR 610.12. RMMs have not been comprehensively validated by most CBBs for this intended use and the noncompliance with FDA regulations is likely attributed to 1) the stringent validation requirements, sometimes difficult to apply to the unique small products, primarily the requirements for sample type or volume; 2) the lack of clear constituents of the validation study for sterility testing of CB products; 3) the fact that CBBs use various CB processing techniques yielding products with different components and thus necessitating the development of a site‐ and product type–specific validation; and 4) the laborious nature of the validation process itself, especially when applying a parallel validation of the RMMs against the CFR/USP method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of CBBs employ growth‐based RMMs for sterility testing in place of the method recommended, described and specified in 21 CFR 610.12. RMMs have not been comprehensively validated by most CBBs for this intended use and the noncompliance with FDA regulations is likely attributed to 1) the stringent validation requirements, sometimes difficult to apply to the unique small products, primarily the requirements for sample type or volume; 2) the lack of clear constituents of the validation study for sterility testing of CB products; 3) the fact that CBBs use various CB processing techniques yielding products with different components and thus necessitating the development of a site‐ and product type–specific validation; and 4) the laborious nature of the validation process itself, especially when applying a parallel validation of the RMMs against the CFR/USP method.…”
Section: Discussionmentioning
confidence: 99%
“…Although the most appropriate sterility test material is the FP, the FDA may allow the use of other material as appropriate and as approved in the BLA application. CB is processed using a variety of technologies, most of which include RBC sedimentation and centrifugation steps to yield RBC and/or plasma‐reduced products . Many laboratories perform sterility testing on plasma discarded during processing.…”
Section: Discussionmentioning
confidence: 99%
“…These studies agreed only for a higher NC loss after wash of thawed products. More recently, two well‐controlled studies compared postthaw cell recovery data and demonstrated superior recovery of CFU‐Cs as a function of the processing method (Table ) …”
Section: Cb Thaw Methodsmentioning
confidence: 99%
“…The PrepaCyte‐CB separation system is a proprietary, antibody‐based (U.S. Patents 6,933,148 and 7,160,723), closed‐system separation kit allowing rapid and specific cell separation . Benefits over conventional methods for cell separation include minimal chemical and physical manipulation of cells resulting in greater cell viability, as well as the closed nature of the system to reduce the risk of contamination, which may have important implications for transplantation .…”
Section: Comparison Of Prepacyte‐cb and Marrowxpress Processing Systementioning
confidence: 99%